Estimating Compensation Due to those Affected by Terrorist Acts - Elamin, Aisha (Journal of Legal Sciences, 2023)
The research aims to study the estimation of compensation due to those affected by terrorist acts, guided by the legal systems in the Kingdom of Saudi Arabia and the experience of the French and Egyptian legislators, beginning with the dispute over the definition of terrorist act, and analyzing the extent of countries’ commitment to compensating those injured by terrorist acts, the legal basis for compensation for damage, and how the injured person is entitled to compensation and its relationship to standards Compensation and how to estimate it.              The research reached several results, including the multiplicity of legal trends in defining a terrorist act, and the most prominent of these trends is the material trend, which focuses on the behavior leading to the crime or its component, and the moral trend, which is concerned with the goal of the terrorist act. The French legislator created a special law for this purpose, but he committed a fund to finance the compensation due for the damages of terrorist acts, and in addition to the Egyptian law, a definition of terrorist acts was established.            The assessment of compensation in the Kingdom of Saudi Arabia depends on a settlement committee formed for this purpose, and unless the law specifies provisions for calculating compensation, the judicial assessment of compensation is subject to the assessment of compensation based on the subsequent damage according to the availability of several basic elements. The assessment of compensation for material damage is relatively easier than others, as the courts were included in In most cases, an expert is appointed to perform that task. Although the expert's opinion is not binding on the court, it is often used as a guide and is considered a reason for the judgment. The court also considers the seriousness of the official's mistake and the extent of its impact on the injured party in estimating compensation.